ANALISIS PROBLEMATIK INDUSTRI DARI JASA WARNET DENGAN METODE KONSTRUK SERVQUAL PARASURAMAN - Muhammad Firmansyah (Akuntansi, 2022)
Internet cafes is a place which provides internet access infrastructure with a variety of connections and using computer as access device so that users can access the Internet and acquire services in the field of information technology. The purpose of this study is to find factors that exist in the service quality cafe business and know the dimensions of service quality are the most influential in the Internet service industry. The method used in the analysis is descriptive analysis Statistik, T test and regression analysis. With the object of a study internet cafes in Malang. From the results of research to know If construct originally by parasuraman etall initially 22 items consisting of 5 dimensions constituent, on a case study in the cafe reduced to 9 items, Gaps on Internet services as measured by the concept servqual. Produce a measure of quality service at the internet cafe. In this study the gaps in the service quality dimensions sequentially from the largest value to the smallest value is Assurance (-1.1115), Empathy (-1.0732), Responsiveness (-0.7834), Tangible (-0.1847) and Reliability (0.0191). Value of r = 1 = 100% means that the quality of service on Internet service can be described by the five constituent dimensionsthat is, empathy, reliability, assurance, responsiveness, and tangible. Standard error of estimate are at zero (0) proves that the regression model appropriate was used to predict the dependent variable or the quality of service.